(untitled) - Brown, William H. (Australia, 2005)
This book provides an exciting introduction to organic chemistry for students majoring in chemistry and in related disciplines, especially the health and biological sciences. In this Fourth Edition, Brown, Foote, and Iverson build on the text's highly-praised hallmarks of unifying mechanistic themes, focusing on problem-solving, using applied problems from the pharmaceutical field, and making innovative use of color and emphasis on visualization. The new edition features increased coverage of mechanisms, more examples of bio-organic chemistry especially relevant to pre-medical students, new in-text learning aids including "How To" boxes, and state-of-the-art text/media integration with the Organic ChemistryNow™ Website.
Hóa hữu cơ 2,Hóa hữu cơ 1
Keywords: Chemistry, organic